Something wild : a novel - Halperin, Hanna (Viking, 2021)
"Told in alternating perspectives that deftly interweave past and present, Something Wild is a magnetic, unflinching portrait of the bond between sisters, as well as a psychologically acute exploration of the legacy of divorce, the ways trauma reverberates over generations, and how it might be possible to overcome the past"--